Rural tourism re-invented: how tourist entrepreneurs implement different notions of rurality. - Kordel, Stefan; Weidinger, Tobias (European rural peripheries revalued: Governance, actors, impacts, 2016)
This paper addresses what strategies tourist entrepreneurs undertake to implement various notions of rurality by means of the example of rural tourism in the Bavarian Forest. In particular, it is asked how hosts enable guests to consume rurality in light of an overall desire to experience a rural life-world in material and immaterial dimensions. Based on empirical data from 41 expert interviews with tourist entrepreneurs, public authorities involved in tourism and local politicians in more than 20 municipalities in the Bavarian Forest, two types of establishments are analysed in this study, i.e., on-farm establishments and wooden accommodations, which refer to regional building culture. Results show that entrepreneurs meet the demand for idyllic notions and modern equipment, following a binary strategy of conservation and re-interpretation. Besides consumption of ruralities, tourists take also part in the process of constructing rurality, for instance when participating in food production. The juxtaposition of tourist structures that reproduce urban-rural dichotomies on the one hand and are influenced by a hybridisisation of the urban and the rural on the other hand, finally encourages diversification of rural tourism sector.